2015
DOI: 10.3390/nano5041667
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Transition Metal Oxides for Supercapacitors

Abstract: Abstract:Recently, transition metal oxides, such as ruthenium oxide (RuO2), manganese dioxide (MnO2), nickel oxides (NiO) and cobalt oxide (Co3O4), have been widely investigated as electrode materials for pseudo-capacitors. In particular, these metal oxides with mesoporous structures have become very hot nanomaterials in the field of supercapacitors owing to their large specific surface areas and suitable pore size distributions. The high specific capacities of these mesoporous metal oxides are resulted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
148
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(150 citation statements)
references
References 85 publications
1
148
0
1
Order By: Relevance
“…However, its large-scale application is limited by the high cost and scarcity of Ru. 8 At present, the environmentally-benign transition metal oxides, such as MnO 2 , NiO, Co 3 O 4 and Fe 3 O 4 , have been found to exhibit excellent redox activity and are readily available; thus, a high energy storage capacity can be obtained at relatively low cost. 8 In contrast, the poor electrical conductivity and slow response of conducting polymer materials results in low power densities and poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, its large-scale application is limited by the high cost and scarcity of Ru. 8 At present, the environmentally-benign transition metal oxides, such as MnO 2 , NiO, Co 3 O 4 and Fe 3 O 4 , have been found to exhibit excellent redox activity and are readily available; thus, a high energy storage capacity can be obtained at relatively low cost. 8 In contrast, the poor electrical conductivity and slow response of conducting polymer materials results in low power densities and poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…3. Wand et al [8] have reported that quasi-rectangular shape of CV arises from unique electrochemical features of electrode active materials, such as reversible redox process, high thermal and chemical stability and pseudo capacitance. The CV curves with same shape at all scan rates also indicate a good capacitive performance of electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Co is found in Figure 5D and the concentration of Ag falls below the detection limit in the same sample. Therefore, the uniform cube-structured particles are the result of Co [25,26].…”
Section: Aqueous Nanoparticle Emissionsmentioning
confidence: 99%